Effect of cardiopulmonary bypass on cytokine network and myocardial cytokine production - Gasz, B. (Clin Cardiol, 2006)
Background: In addition to the well‐investigated proinflammatory cytokine expression, there is an ever increasing interest in the field of anti‐inflammatory response to cardiopulmonary bypass (CPB). Evidence suggests that myocardium serves as an important source of cytokines during reperfusion and application of CPB. The effect of coronary artery bypass graft (CABG) without CPB on myocardial cytokine production has not as yet been investigated. Hypothesis: Cardiopulmonary bypass can cause long‐term disturbance in pro‐ and anti‐inflammatory cytokine balance, which may impede a patient's recovery following surgery. Therefore, the effect of CPB on the balance of the pro‐/anti‐inflammatory cytokines network and myocardial cytokine outflow was assessed throughout a longer period after surgery. Methods: Twenty patients were scheduled for CABG with CPB and 10 had off‐pump surgery. Blood samples were taken before, during, and over the first week following surgery. Coronary sinus blood samples were collected during surgery. The ratio of pro‐ and anti‐inflammatory cytokines was calculated and the cytokine concentration of peripheral and coronary sinus blood were compared in both groups. Results: Pro‐/anti‐inflammatory cytokine ratio decreased early after CPB followed by a delayed and marked increase. A more balanced ratio was present following off‐pump surgery. Coronary sinus levels of certain cytokines exceeded the concentration of systemic blood in the course of CPB but not during off‐pump operation. Conclusion: Patients show pro‐inflammatory predominant cytokine balance at a later stage after CPB in contrast to those without CPB. The heart produces a remarkable amount of cytokines only in the course of surgery with CPB.